Digital Citizenship, Media Literacy, and the ACTS Framework. (31st May 2022) - von Gillern, Sam; Gleason, Benjamin; Hutchison, Amy
Abstract: In a "post‐truth" era in which misinformation permeates digital environments, it is critical for teachers to help students develop media literacy skills by analyzing and evaluating media messages. Through these processes, English language arts teachers can also help students develop digital citizenship skills, in which they can analyze media, create messages, and then share their creations. These skills and processes empower students to become informed digital citizens who actively engage in civic processes and advocate for issues and actions in which they believe. This article explores the concepts of digital citizenship and media literacy and presents the Analyze, Create, Then Share Framework as a way to help students develop skills in these areas. Analyzing, Creating, Then Sharing media messages can aid students' understanding of disciplinary content, help students participate in civic processes, and promote digital citizenship.